2014
DOI: 10.1002/chem.201403281
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Donor Selectivity of D‐Fructose‐6‐Phosphate Aldolase for Biocatalytic Asymmetric Cross‐Aldol Additions of Glycolaldehyde

Abstract: D-Fructose-6-phosphate aldolase (FSA) is a unique catalyst for asymmetric cross-aldol additions of glycolaldehyde. A combination of a structure-guided approach of saturation mutagenesis, site-directed mutagenesis, and computational modeling was applied to construct a set of FSA variants that improved the catalytic efficiency towards glycolaldehyde dimerization up to 1800-fold. A combination of mutations in positions L107, A129, and A165 provided a toolbox of FSA variants that expand the synthetic possibilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 51 publications
3
56
0
Order By: Relevance
“…Notably, inversion of the stereochemistry at C3 (that defined during the approach of the acceptor aldehyde to the FSA-donor intermediate) in the first addition of 1a would afford L-glucose, a non-caloric sweetener of complex preparation by alternative procedures 32 . Such C3 inversion appeared feasible, because the stereochemical approach of the aldehyde to the aldolase-donor complex is often compromised when dealing with non-natural substrates 26,33 and it has been successfully inverted by engineering several aldolases 34 . In a preliminary exploration, we observed that dimerization of 1a with FSA A165G provided an ∼4:1 mixture of D-threose (2a) and L-erythrose (4a), as inferred from chromatographic and NMR analysis (Supplementary Table 28 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Notably, inversion of the stereochemistry at C3 (that defined during the approach of the acceptor aldehyde to the FSA-donor intermediate) in the first addition of 1a would afford L-glucose, a non-caloric sweetener of complex preparation by alternative procedures 32 . Such C3 inversion appeared feasible, because the stereochemical approach of the aldehyde to the aldolase-donor complex is often compromised when dealing with non-natural substrates 26,33 and it has been successfully inverted by engineering several aldolases 34 . In a preliminary exploration, we observed that dimerization of 1a with FSA A165G provided an ∼4:1 mixture of D-threose (2a) and L-erythrose (4a), as inferred from chromatographic and NMR analysis (Supplementary Table 28 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…28a-c). Attempts to engineer the most active FSA variants 26 to form L-erythrose (for example, library FSA L107Y/A129G/A165G/S166X ) were unsuccessful. In a second step, a set of FSA variants was assayed for selective aldol addition of 1a to L-erythrose (4a) (Supplementary Table 28).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations